Marine ecosystem services: Perceptions of indispensability and pathways to engaging citizens in their sustainable use. (November 2015) - Blasiak, Robert; Yagi, Nobuyuki; Kurokura, Hisashi; Ichikawa, Kaoru; Wakita, Kazumi; Mori, Aimee
Abstract: Research on attitudes towards the conservation and sustainable use of natural systems has predominantly focused on terrestrial systems. While marine systems provide crucial ecosystem services that support human well-being, some are significantly more tangible in people's everyday lives, leading to more complex perceptions of their value. An assessment of perceptions about marine ecosystem services as well as willingness to engage in the conservation and sustainable use of these ecosystem services through taxation, donation, volunteering, or other activities is provided here based on a randomized survey of 1434 residents of the USA. Statistical analysis is presented, which suggests that: (1) respondents view oceans as a truly global commons with little distinction between the national and international indispensability of the ecosystem services they provide; (2) among the options for engaging citizens in the sustainable use of ecosystem services, respondents were most averse to taxation, a trend that is strongly correlated with age and more weakly correlated with gender; (3) perceptions about the potential loss of ecosystem services are a much stronger indicator for willingness to engage in their sustainable use than perceptions about the current status of the ecosystem services; (4) there is little or no correlation between political leanings and geographical location of respondents and their perceptions of marine ecosystem services or readiness to engage in their conservation and sustainable use. Among other things, these findings provide a basis for developing policies aimed at maximizing public engagement in sustainable management of marine ecosystem services, while identifying mechanisms most likely to meet with resistance from the general public. Highlights: People see oceans as a global commons without national/international distinctions. Political leaning uncorrelated with interest in sustainable use of marine ecosystems. High aversion found towards taxation, with strong age and weak gender correlations. Perceived indispensability of marine ecosystem services linked to readiness to act.